PENGARUH KOMPETENSI PEDAGOGIK GURU DAN FASILITAS BELAJAR TERHADAP PRESTASI BELAJAR MELALUI MOTIVASI BELAJAR - Setiadi, Devi; Setiyani, Rediana (Economic Education Analysis Journal, 2018)
Tujuan penelitian ini adalah untuk mengetahui pengaruh persepsi siswa mengenai kompetensi pedagogik guru dan fasilitas belajar terhadap prestasi belajar siswa pada mata pelajaran ekonomi melalui motivasi belajar. Populasi penelitian ini adalah seluruh siswa kelas XI IPS SMA Negeri 15 Semarang tahun ajaran 2016/2017 yang berjumlah 110 dengan sampel sebanyak 87 siswa. Metode pengumpulan data menggnakan angket (kuesioner). Metode analisis data yang digunakan adalah analisis deskriptif dan analisis lajur. Hasil penelitian menunjukkan bahwa persepsi siswa mengenai kompetensi pedagogik guru, fasilitas belajar, dan motivasi belajar berpengaruh positif dan signifikan terhadap prestasi belajar siswa. Motivasi belajar dapat memediasi perpepsi siswa mengenai konpetensi peagogik guru dan fasilitas belajar terhadap prestasi belajar siswa. Secara simultan persepsi siswa mengenai kompetensi pedagogik guru dan fasilitas belajar terhadap prestasi belajar ekonomi sebesar 72%, secara parsial kompetensi pedagogik terhadap prestasi belajar ekonomi berpengaruh sebesar 22%, fasilitas belajar berpengaruh 31% terhadap prestasi belajar, dan motivasi belajar berpengaruh sebesar 37% terhadap prestasi belajar Therefore this study aimed to determine the partial and simultaneous effects between entrepreneurship education, business center and creativity on the students' entrepreneurial spirit.The population was the eleventh grade students of the marketing class of SMK Negeri 1 Slawi which amounted 134 students with a total sample of 58 students calculated by Slovin formula. Data collection methods were using questionnaires. Data analysis methods used percentage descriptive analysis and multiple regression analysis. The results showed that entrepreneurship education partially affected the students' entrepreneurial spirit by 8.24%, business center partially affected the students' entrepreneurial spirit by 31.58%, creativity partially affected the students' entrepreneurial spirit by 10.3% and entrepreneurship education, business center and creativity affected imultaneously the students' entrepreneurial spirit by 65.8%.The conclusions from this study are that there is an influence between entrepreneurship education, business center and creativity influencing the students' entrepreneurial spirit both partially and simultaneously. Suggestions are that the school should provide school programs that can encourage students' creativity such as holding an annual event involving all students, then educators, especially in marketing department and entrepreneurship subject teachers, are advised to improveand maintain the quality of their teaching, and for further researchers who are interested in the same research theme, they are expected to expand the object of research and add other independent variables outside the independent variables contained in this study